Endophytic fungi of wild banana (Musa acuminata) at Doi Suthep Pui National Park, Thailand - Photita W. (2014)
Endophytic fungi were isolated from 7500 samples of wild Musa acuminata collected from five sites at Doi Suthep Pui National Park, Thailand during December 1998 to July 1999. Overall colonization rates from surface sterilized tissues were 56.5, 48.9, 48, 47.9 and 41.7% for the Medicinal Plant Garden, Ban Suthep, Queen Sirikit Botanic Garden, San Gu, and Montatarn waterfall sites respectively. Sixty-one different fungal taxa were isolated. Fewer isolates were recovered from younger than older samples. Xylariaceous taxa and Guignardia cocoicola were the most frequently isolated endophytes from leaves and were either absent or rare in midrib, petiole and pseudostem. Colletotrichum gloeosporioides, C. musae, Guignardia cocoicola, various sterile mycelia and xylariaceous spp. were common at all sites. The endophyte fungal communities at the five sites were found to differ. Deightoniella torulosa was the most frequent isolate at the Ban Suthep site and was either absent or rare at other sites. Colletotrichum species were most common in the midribs and petioles at all sites, while Pyriculariopsis parasitica and Dactylaria sp. were most common in the pseudostems. The endophyte communities isolated from M. acuminata in this study are compared with those from previous studies on tropical hosts. Several of the endophytes isolated are established pathogens of banana and provide support for the hypothesis that some endophytes are latent pathogens. The diversity of fungi on banana is discussed in relation to global estimates of numbers of fungus species.